Retos de los Objetivos de Desarrollo Sostenible en ciudades y territorios del siglo XXI - Córdoba Hernández, Rafael; Durán, María Sofía (Territorios en formación, 2019)
Retos de los Objetivos de Desarrollo Sostenible en ciudades y territorios del siglo XXI